COMRADESHIP: CURATING, ART, AND POLITICS IN POST-SOCIALIST EUROPE - Behar, Ionit (Revista VIS: Revista do Programa de Pós-Graduação em Artes Visuais, 2020)
Comradeship: Curating, Art, and Politics in Post-Socialist Europe compiles fifteen essays written by Slovenian curator, museum director, and scholar Zdenka Badovinac dating from 1998 to 2018.